Transport Proteins Regulate the Flux of Metabolites and Cofactors Across the Membrane of Plant Peroxisomes - Linka, Nicole; Esser, Christian (Frontiers in Plant Science, 2012)
In land plants, peroxisomes play key roles in various metabolic pathways, including the most prominent examples lipid mobilization and photorespiration. Given the large number of substrates that are exchanged across the peroxisomal membrane, a wide spectrum of metabolite and cofactor transporters is required and need to be efficiently coordinated. These peroxisomal transport proteins are a perquisite for metabolic reactions inside plant peroxisomes and the entire peroxisomal “permeome” is closely linked to the adaption of photosynthetic organisms during land plant evolution to fulfill and optimize their new metabolic demands in cells, tissues, and organs. This review assesses for the first time the distribution of these peroxisomal transporters within the algal and plant species underlining their evolutionary relevance. Despite the importance of peroxisomal transporters, the majority of these proteins, however, are still unknown at the molecular level in plants as well as in other eukaryotic organisms. Up to date, four transport proteins have been recently identified and functionally characterized in Arabidopsis so far: One transporter for the import of fatty acids and three carrier proteins for the uptake of the cofactors ATP and NAD into plant peroxisomes. The transport of the three substrates across the peroxisomal membrane is essential for the degradation of fatty acids and fatty acids-related compounds via β-oxidation. This metabolic pathway plays multiple functions for growth and development in plants that has been crucial for during land plant evolution. Here, we describe the current state of their physiological roles in Arabidopsis and discuss novel features in their putative transport mechanisms.